The Rise of Racism and Xenophobia During the COVID-19 Pandemic as an Expression of Their Centuries-Old History – A Sociological and Security Aspect - Hasković, Edita (Kriminalističke teme, 2022)
Extremely complex crisis that occurred after the proclamation of the COVID-19 pandemic in March 2020, contributed to the escalation of racism and xenophobia in the international arena. Their current rise must be observed from the perspective of the historically established pattern of connecting minorities, racial groups and certain communities with infectious diseases, which has made racist and xenophobic approaches and narratives indispensable constituents of responses to them. The stigma of the disease, as history confirms, is a permanent companion to the outbreak of infectious diseases, thus the coronavirus pandemic was no exception. The radicalization of public discourse through nativism, hatred and fear during the current health crisis, with the significant support of some mainstream media, was in the forefront contributed to by neo-nationalist forces. They exploited the insecurity and uncertainty generated by the pandemic to project fear of the other and different with their obligatory emanation as potential threats. Even though the COVID-19 pandemic contributed primarily to the reaffirmation of racism and xenophobia against the Chinese and Asians, which was supported by the coronavirus provenance, it undoubtedly paved the way for a general racist and xenophobic discourse.